THE EFFECTIVENESS OF USING TASK BASED LANGUAGE TEACHING (TBLT) IN TEACHING THE STUDENTS’ ENGLISH SPEAKING ABILITY AT THE ELEVENTH GRADE OF SMK PENERBANGAN AAG ADISUTJIPTO YOGYAKARTA - Yasmika Baihaqi (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2016)
This study is intended to find out that the task based language teaching method is effective in improving the students’ speaking ability at the eleventh grade students of SMK Penerbangan AAG Adisutjipto Yogyakarta in the academic year 2012/ 2013. The population of this research is the eleventh grade students of SMK Penerbangan AAG Adisutjipto Yogyakarta in the academic year 2012/ 2013. The researcher in this case takes two intact classes with a total number of 63 students selected as the samples of the study. To collect the data, the researcher utilizes a test and questionnaire. The test is employed to reveal the students’ speaking ability while the questionnaire is used to collect the data of the students’ learning activities during the teaching and learning process. The data are analyzed utilizing descriptive and inferential statistics. The task based language teaching (TBLT) method is effective on the students’ speaking ability at the eleventh grade students of SMK Penerbangan AAG Adisutjipto Yogyakarta in the academic year 2012/ 2013. It is supported from the mean of the pre test and post test for experimental group and control group. This study yields the mean in pre-test for experimental group is 37.13 and 34.71 for control group. In the post test, the mean of the experimental group becomes 69.13 and 37.94 for control group. The t-test value showed 20.509 with the degree of freedom 62. It was higher than the value of t-table (2.000) at the significant level of 0.05. It means that TBLT method is more effective than teacher’s own method to teach speaking. .